Ammonia nitrogen recovery from biogas slurry by SCP production using Candida utilis. (1st January 2023) - Ding, Hongxia; Li, Jiabao; Deng, Fang; Huang, Siyuan; Zhou, Pan; Liu, Xiaofeng; Li, Zhidong; Li, Dong
Abstract: The safe and robust yeast Candida utilis was employed for nitrogen recovery as single cell protein from biogas slurry. The maximum biomass of 6.2 g/L with protein content of 53.5% was produced in batch cultivation with glucose as the carbon source, C/N ratio of 3:1, NH4 + -N concentration of 3000 mg/L, initial pH of 8.0, and the addition of 0.35% (w/v) Na2 HPO4 . It was speculated that C. utilis can grow well with free ammonia below 197 mg/L. In fed-batch fermentation, a biomass of 14.8 g/L was obtained, and the maintenance of aerobic conditions was critical to improving the production of single cell protein. The sterilized and non-sterilized biogas slurry can be used as an effective pH regulator. The obtained single cell protein was a nutritious, safe, and reliable protein source. This study provides novel insights into nitrogen recovery via C. utilis as a single cell protein from biogas slurry. Graphical abstract: Image 1 Highlights: Candida utilis was first used for nitrogen recovery as SCP from biogas slurry. The maximum biomass of 14.8 g/L with a protein content of 46.5% was achieved. The maintenance of aerobic conditions was critical to improve the SCP production. Biogas slurry could be used as an effective pH regulator. The SCP contains 21 amino acids, and the heavy metal met the feed standards.